COMPARISON OF VAPOR-PHASE ACETIC ACID AND VINEGAR EFFECTIVENESS IN MAINTAINING QUALITY OF SWEET BASIL (OCIMUM BASILICUM LINN.) - Montinee Teerarak; Soraya Kerdpiboon; Warawut Krusong (My University, 2020)
Leafy shoots of sweet basil (Ocimum basilicum Linn.) were exposed to the vapor of either dilute acetic acid (AA) or of upland rice vinegar (URV) – both solutions were diluted to contain 4% of acetic acid – for 10 min and stored at 12°C. The sweet basil exposure to AA had a 16% increase in shelf life and those exposures to URV 35% increase compare to the control. There were no significant differences in fresh weight loss during storage between the AA and URV but both had significantly lower fresh weight losses than the control. The chlorophyll content of both AA and URV were significantly higher than the control. The radical scavenging was significantly higher in the URV than in the AA and the control. The electrolyte leakage was both significantly lower in the URV than in the AA and the control. The occurrence of lipid peroxidation was similar in both the AA and URV, and both were significantly lower than in the control. These results indicate URV has potential as an effective way of raising quality and extending postharvest storage of sweet basil shoots.
Keywords: Sweet Basil; Essential Oils and Antimicrobial Activity